2015
DOI: 10.1590/s1517-707620150002.0030
|View full text |Cite
|
Sign up to set email alerts
|

Potencialidades computacionales del Método de los Elementos Finitos para la modelación y simulación de materiales compuestos: revisión

Abstract: RESUMENEn este trabajo se presenta una revisión bibliográfica de modelos computacionales que utilizan el Método de los Elementos Finitos (MEF) para el estudio del comportamiento mecánico de los materiales compuestos, enfocándose el análisis en materiales reforzados por partículas o fibras. El análisis realizado muestra que el MEF permite estimar, de manera efectiva, la influencia sobre las propiedades mecánicas de los materiales compuestos, de factores como el reforzante, su fracción volumétrica, orientación, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…3, 4 and 5. In case of the implementation of the symmetry boundary conditions on the rectangular and cubic prisms including the fibers which were embedded into the matrix material (RVE) unit-cell method was developed [9]. In the consideration of the mechanical P [N] and displacement δ [µm] based loadings, the obtained elastic constants were reached to different values that were mentioned in literature.…”
Section: Micromechanical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…3, 4 and 5. In case of the implementation of the symmetry boundary conditions on the rectangular and cubic prisms including the fibers which were embedded into the matrix material (RVE) unit-cell method was developed [9]. In the consideration of the mechanical P [N] and displacement δ [µm] based loadings, the obtained elastic constants were reached to different values that were mentioned in literature.…”
Section: Micromechanical Modelingmentioning
confidence: 99%
“…Jiang et al [8] reported that the ratio of surface-to-surface distance of adjacent carbon nanotubes (CNTs) to the CNT diameter plays a key role in improving the overall elastic modulus of the CNTreinforced composites when the tubes were perfectly aligned, completely separated from other tubes, and ideally bonded with the composite matrix. Alfonso et al [9] presented a review-research about the computational potentialities of the FEM for the modeling and simulation of composite materials. This review showed that the most studied property was the Young modulus and geometric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Un software de elementos finitos como ANSYS contienen herramientas que permiten el modelado y la simulación de un gran número de fenómenos, estructuras y materiales, para lo cual divide su operación en etapas o módulos, donde generalmente se definen aspectos tales como geometría del modelo, tipos de elementos en los que se dividirá, asignación de propiedades de los materiales y generación de la malla para definir los nodos y uniones entre elementos. (Gurunath, 2015;Alfonso et al, 2015;Ramírez y Rodan, 2016;Muhammad et al, 2020).…”
Section: Introductionunclassified
“…Experimental studies were also performed to support the numerical results [8]. Two-dimensional (unit cell method) and three-dimensional finite element analysis (FEA) with RVE was performed, and results were compared with the results of experimental studies in the literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Researchers often used the following FE commercial codes: ABAQUS [11,12,16,19], ANSYS [17,20], NASTRAN [13], and ALGOR-FEAS [9].…”
Section: Introductionmentioning
confidence: 99%